People with Disabilities Leading the Design of Serious Games and Virtual Worlds. - Yurgos Politis; Nigel Robb; Anita Yakkundi; Karola Dillenburger; Nicola Herbertson; Beth Charlesworth; Lizbeth Goodman (Serious Games Society, 2017)
Games and virtual worlds have many potential benefits for people with intellectual disabilities (ID) and autism spectrum disorder (ASD), in terms of training, education, and rehabilitation. However, because this population presents a wide range of specific needs and abilities, it can be difficult to design games which are engaging and present optimum levels of challenge to players. By including individuals with ID and ASD in the design phase we can help meet their specific needs and preferences by personalizing an intervention through the exploration of experimental techniques, methods and assistive technologies. By embracing the Responsible Research and Innovation approach, we bring science and society closer together to shape the world for future generations. A number of approaches for achieving such inclusion have been described, such as User Sensitive Inclusive Design, Universal Design, and Design for All. Here we discuss three specific examples of the design of games and virtual worlds for people with ID/ASD and illustrate how they attempt to meet their needs. Namely 1) a blended approach of computerised program and applied behaviour analysis for reading skills 2) immersive gameplay for employment and transferable skills training and 3) virtual reality training to enhance communication skills.